Environmental Trends Among Tishreen University Students (A comparative study between students of the College of Education and students of the College of Medicine) - سمر شبيب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the current research is to know the nature of environmental trends among the students of Tishreen University in the city of Lattakia and to reveal the differences between the members of the research sample according to the variables of the type of college (education - medicine) and the academic year (first - last). The research sample consisted of (212) male and female students, including (112) students from the College of Education and (90) students from the College of Medicine, distributed over the first and last academic years. To achieve the goal of the research, the scale of environmental trends prepared by (Shribe et al., 2016) was used, which is codified for the students of Tishreen University. The researcher also followed the descriptive approach, and the results of the research indicated that the environmental trends among the members of the research sample were negative and not friendly to the environment. study for the benefit of students of the last years